2009
DOI: 10.1186/1471-2407-9-366
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tyrosine-phosphorylated proteins associated with metastasis and functional analysis of FER in human hepatocellular carcinoma cells

Abstract: Background-Aberrant activity of tyrosine-phosphorylated proteins is commonly associated with HCC metastasis. Cell signaling events driven by these proteins are implicated in numerous processes that alter cancer cell behavior. Exploring the activities and signaling pathways of these proteins in HCC metastasis may help in identifying new candidate molecules for HCC-targeted therapy.Methods-Hep3B (a nonmetastatic HCC cell line) and MHCC97H (a highly metastatic HCC cell line) were used in this study, and the tyros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 74 publications
1
56
0
Order By: Relevance
“…FER is expressed ubiquitously in a variety of tissues and cells (16) and is expressed at a higher level in numerous malignant cell lines than the corresponding normal cells (34)(35)(36). FER expression has been linked to prostate cancer, with higher levels in extracts from cancers compared with normal or hyperplasic tissues (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…FER is expressed ubiquitously in a variety of tissues and cells (16) and is expressed at a higher level in numerous malignant cell lines than the corresponding normal cells (34)(35)(36). FER expression has been linked to prostate cancer, with higher levels in extracts from cancers compared with normal or hyperplasic tissues (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have identified Fer activation or upregulation in a number of different cancers, including lung (14), hepatic (15), prostate (16), and triple-negative breast cancer (17). Overexpression of Fer was also linked to quinacrine resistance and enhanced activation of NFkB pathway (5).…”
Section: Introductionmentioning
confidence: 99%
“…At the clinical level, high Fer expression levels have been linked to poor prognosis of hepatocellular carcinoma (HCC; ref. 28), clear cell renal cell carcinoma (29,30), postoperative NSCLC (25), and high-grade basal/triple-negative breast cancer (26).…”
Section: Introductionmentioning
confidence: 99%